2002
DOI: 10.1111/j.1365-2621.2002.tb08843.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐induced Changes in Angel Food Cakes Containing Egg‐white Protein or Whey Protein Isolate

Abstract: Angel food cakes made from egg white or whey protein foams were compared. Cakes were evaluated based on final volume, dynamic volume change, and rheological transitions during baking. Cake expansion during baking was a function of protein concentration regardless of protein type. Cakes containing whey proteins had a lower ability to prevent collapse once starch gelatinization started during baking. Heat-treating whey proteins or adding xanthan gum increases cake volume, but not to the extent of egg-white prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 20 publications
(10 reference statements)
1
46
0
3
Order By: Relevance
“…Protein denaturation and starch gelatinization occur during heating, therefore contributing to the formation of a solid cake matrix. Accordingly, the final cake volume and cake structure depend on the interaction of these processes (Pateras et al, 1994;Pernell et al, 2002).…”
Section: Tablementioning
confidence: 99%
“…Protein denaturation and starch gelatinization occur during heating, therefore contributing to the formation of a solid cake matrix. Accordingly, the final cake volume and cake structure depend on the interaction of these processes (Pateras et al, 1994;Pernell et al, 2002).…”
Section: Tablementioning
confidence: 99%
“…This was expected and a similar finding was obtained in Abdul Hussain andAl-Oulabi (2009), DeVilbiss et al (1974), and Mohamed et al (1995), who reported that whey protein as egg alternative has resulted in lower cake volume. Besides poor batter stability (Pernell et al 2002), Penfield and Campbell (1990) explained that the lower cake volume was due to the lower batter viscosity (Fig. 1a), which was not sufficiently viscous to minimize the coalescence of gas bubbles and hence caused the loss of leavening gases during baking as large bubbles rise to the surface and escape.…”
Section: Viscoelastic Properties Of Battermentioning
confidence: 99%
“…Unfortunately, the baked cake product quality was not comparable with fully egg white formulated cakes. In the study of total whey protein replacement in angel food cakes, cakes containing whey protein were smaller in volume due to the lower stability of cake batter to help in prevention of cake collapse (Pernell et al 2002). Partial replacement of egg white protein with whey protein isolate in angel food cake also showed an overall poorer quality, with lower cake volume and coarser bubbles structure, which was probably due to the higher denaturation temperature of whey protein that resulted in higher coagulation temperature and caused over-expanded gas cells in cake batter to collapse during baking (Arunepanlop et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cakes were made using the method of Pernell et al 10 Foams were generated from solutions containing 12.8% 10× powdered sugar. Cake flour and 10× powdered sugar were sifted three times and then folded into the whipped foam (solutions included sugar) using 20 strokes of a balloon whisk.…”
Section: Cake Preparationmentioning
confidence: 99%